Dampak profitabilitas terhadap income smoothing dengan rasio kas sebagai variabel moderasi pada perusahaan manufaktur yang terdaftar di BEI periode 2020-2024 - Ni Putu Karinina Febriyanty; Khairunnisa; Defel Septian (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
Continued implementating of profit smoothing, which is a management effort to stabilize financial performance reported to external parties. The purpose of this research is to examine how Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) affect income smoothing practices, with cash ratio acting as a moderating variable. This study focuses on manufacturing companies listed on the Indonesia Stock Exchange during the period from 2020 to 2024. The research sample includes 94 companies selected using the purposive sampling method. The analysis methods used include descriptive statistics, classical assumption tests, and moderated regression analysis using the quasi-moderated regression approach. The research results show that ROA and NPM do not significantly affect income smoothing practices, while ROE has a positive and significant effect. In addition, the cash ratio is not able to moderate the relationship between ROA, ROE, and NPM with income smoothing. This study contributes to theory by strengthening the perspective of agency regarding managerial conflict of interest, and it also offers practical benefits for investors, managers, and regulators in improving awareness of financial reporting quality, especially for companies with high return on equity.